Pleural effusion: a potential surrogate marker for higher-risk patients with acute type B aortic dissections. (30th December 2021) - Reutersberg, Benedikt; Trimarchi, Santi; Gilon, Dan; Kaiser, Clayton; Harris, Kevin; Shalhub, Sherene; Reece, T Brett; Nienaber, Christoph; Ehrlich, Marek; Isselbacher, Eric; De Oliveira, Nilto; Montgomery, Daniel; et al.
Abstract: OBJECTIVES: Pleural effusions (PEffs) are known to occur in type B acute aortic dissection (TBAAD). We investigated the relationship between pleural effusion and the development of early or late complications following TBAAD. METHODS: The incidence of PEff (defined as at least an obliteration of the costophrenic angle in a frontal projection) diagnosed on their initial chest X-ray in patients with TBAAD enrolled in the International Registry of Acute Aortic Dissection was examined. We analysed in-hospital outcomes and long-term survival separately for patients with and without PEffs (PEff+ versus PEff−, respectively). RESULTS: Included were 1252 patients with TBAAD, of whom 224 (17.9%) had PEff. Compared with patients without PEff in the initial chest X-ray, these were significantly older [mean age 67 (SD: 14.7) vs 63.4 (SD: 14.2) years, P  = 0.001] and more often female (42.4% vs 34.2%, P  = 0.021) and had more comorbidities (known aortic aneurysm, chronic obstructive pulmonary disease, chronic renal failure, diabetes, congestive heart failure or mitral valve disease). PEff was associated with higher in-hospital mortality (16.1% vs 9.1%, P  = 0.002) and increased rates of neurological complications (16.6% vs 11.1%, P  = 0.029), acute renal failure (27.2% vs 19.7%, P  = 0.017) and hypotension (17.4% vs 9.6%, P  = 0.001). In addition, patients with PEff underwent aortic repair more frequently (44.6% vs 32.5%, P  < 0.001). In the long-term patients with PEff showed lower 5-year post-discharge survival (67.6% vs 77.6%, P  = 0.004). Multivariable analysis with propensity-matched data showed that PEff was not an independent risk factor for in-hospital mortality (odds ratio 1.9, 95% CI 0.8–4.4, P  = 0.141). CONCLUSIONS: Patients with TBAAD and evidence of PEff showed a higher in-hospital mortality, are more likely to develop additional in-hospital complications and have a decreased likelihood of survival during follow-up. However, according to propensity-matched analysis, PEff remained not as an independent predictor of worse outcome but might serve as an early surrogate marker to identify higher-risk patients. Abstract : According to current guidelines, intervention for acute type B aortic dissection (TBAAD) is recommended in case of complications.